Analysis of consumer behavior and energy calculation for phase end of life on stamped batik products - Djunaidi, Much.; Ayuningtyas, Dyah (Sustinere: Journal of Environment and Sustainability, 2018)
A product will enter the end of life phase when the usage period expires. End of life recycleis divided into three categories, namely reuse, recycle, and landfills. Reuse is transferring usage rights to others to be used for the same purpose. Recycle is utilising used goods as raw materials for other products. Landfills are putting used clothing to a garbage dump site. Consumers have different tendencies to the expired product. Stamped batik as a typical product of Solo also experiences the same treatment at the end of its life. This study has the objective of reviewing the consumer behaviour toward the stamp batik and calculating the energy needed in the final product period. Simapro 3.8.0.0 sofwate was used for the analysis. Based on consumer behaviour toward the end of product life, the stamped batik user mostly transfer the function of stamped batik to cleaning cloth or recycle (48.97%). The energy needed for the recycling process of stamped batik is 3.2 kPt. The energy resources of the landfill of stamped batik are 0,085 kPt. The electrical energy used for landfills of stamped batik is  14.4 MJ per year.